Analisis Strategi Mahasiswa dalam Menjaga Kebugaran Pasca Pandemi Covid-19 - Erna Yantiningsih; Rahmat Putra Perdana; Eka Supriatna; Novi Yanti; Witri Suwanto; Dody Tri Iwandana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to discover how knowledge related to the Covid-19 virus and fitness during the Covid-19 pandemic. Quantitative descriptive research with the type of data collection using a questionnaire in the form of a closed questionnaire. The results showed that data on the variable knowledge of Covid-19 with four alternative answers indicated that the very high category was 89 respondents with a percentage value of 56%, and the high category was 71 respondents with a percentage value of 44%. Then the physical fitness variable shows that the very high category is 38 respondents with a percentage value of 23.75%, the high category is 118 respondents with a percentage of 73.75%, and the low category is four respondents with a percentage of 2.5%. In conclusion, knowledge about Covid-19 is in the very high category, and learning about physical fitness is in the high category. Keywords: Covid-19, Physical Fitness, Post-Pandemic,